O amor em Dáfnis e Cloé : as traduções de Jacques Amyot (1559), Paul-Louis Courier (1810) e Roberto Freire (1965) - Igor Barbosa Cardoso (2019)
In Giles Barber’s words, Daphnis and Chloe is an “unknown bestseller”. The terms used by the author are insightful, simultaneously expressing the underground and fruitful pathway of the Ancient text in Modern History. Since the 16th century the idyllic love as devised by Longus has worked both as a role model and an inspiration for future cultural production, even though it has not always been recognized as such. This is the case of Roberto Freire, who is often remembered as the creator of somatherapy. Freire is also the writer of Cleo e Daniel (1965), which plot involves the translation of Daphnis and Chloe into Portuguese. More than a simple reference to the Ancient text, Freire considered, at various times, the importance of Longus for the formulation of his ideas. However, not even Cleo e Daniel’s sales success endorsed analysis that effectively approach the distant past in relation to this recent past. Was there any presence of the ancient passion between the two young lovers in the elaboration of Freire’s therapy? This doctoral dissertation does not answer this question in particular. However, it can work as an intriguing starting point for this as it addresses the reformulation of the Ancient idyll in Freire’s novel, as well as in his first artistic production (on theater and soap opera), in view of the social and political upheavals that took place in Brazil. In order to do so, the dissertation first inquires what Freire could effectively mobilize from Longus’ writings. Between the 2nd and 20th centuries, the text passed through a myriad of cultural mediations, which sometimes suppressed and in others added values, programs and imaginary – and not only words – to the Ancient novel. Two French translations had a major importance. Longus’ first vernacular edition was Les amours pastorales (1559), by Jacques Amyot. With Daphnis et Chloé (1810), Paul-Louis Courier resumed the first translation to correct passages considered unfaithful to the Ancient text. He also introduced a new passage from Daphnis and Chloé – hitherto lost – in an unfortunate episode that ended damaging the important manuscript of Florence. Comparing the three translations with the Ancient text, this dissertation does not seek to unravel the “original”. It aims to highlight the importance of Classical Reception Studies on understanding modern problems and, ultimately, the role it has on understanding Ancient History itself. Lastly, the dissertation expresses the relevance of the Ancients among us.